PIRAMIDA UANG ITU ADALAH PERDAGANGAN ORANG: Eksploitasi Perempuan dan Anak Perempuan - Sri Nurherwati (Institut Filsafat dan Teknologi Kreatif Ledalero, 2014)
The author, a member of the National Commission on Violence against Women, presents data from the Commission on domestic violence and the trafficking of women and girls over the past dozen years (2001-2013). Through false promises of well paying jobs and the provision of false documents, the trafficking victims, often already in debt in their home of origin, are lured into further debt in their distant place of forced employment. Sexual exploitation is never far from physical and emotional violence. Kata-kata Kunci: Komnas Perempuan, korban kekerasan, perdagangan orang, pelaku kekerasan, pemalsuan, perlindungan TKI.